E44Q mutation in NaV1.7 in a patient with infantile paroxysmal knee pain: electrophysiological analysis of voltage-dependent sodium current. Issue 6 (June 2021) - Takahashi, Kiichi; Ohba, Takayoshi; Okamoto, Yosuke; Noguchi, Atsuko; Okuda, Hiroko; Kobayashi, Hatasu; Harada, Kouji H.; Koizumi, Akio; Ono, Kyoichi; Takahashi, Tsutomu
Abstract: Gain-of-function mutations in voltage-gated sodium channels (NaV 1.7, NaV 1.8, and NaV 1.9) are known causes of inherited pain disorders. Identification and functional assessment of new NaV 1.7 mutations could help elucidate the phenotypic spectrum of NaV 1.7 channelopathies. We identified a novel NaV 1.7 mutation (E44Q in exon 2) that substitutes a glutamic acid residue for glutamine in the cytoplasmic N-terminus of NaV 1.7 in a patient with paroxysmal pain attacks during childhood and his family who experienced similar pain episodes. To study the sodium channel's function, we performed electrophysiological recordings. Voltage-clamp recordings revealed that the mutation increased the amplitude of the non-inactivating component of the sodium current, which might facilitate channel opening. These data demonstrate that E44Q is a gain-of-function mutation in NaV 1.7, which is consistent with our patient's pain phenotype. Abstract : NaV 1.7; Paroxysmal pain; Patch-clamp techniques; SCN9A mutation; Voltage-gated sodium channel.